Limnology of two freshwater ponds of Imphal, Manipur - Gupta, M Das (Indian Journal of Fisheries, 2011)
Our knowledge on the limnology of theponds of the North-Eastern India, speciallyManipur, is rather poor. The present studyhas been undertaken to know the seasonalvariations in the abiotic condition and alsoto know the biological condition of 2 pondsof Manipur.